Calculating of the Electric Transition Forces and Radii of Even-even- Nuclei of Cadmium (100-12448Cd ) Cd Isotopes - Mohsin Ibrahim, Safa; Ahmed Ebrahiem, Sameera; Ben Rhaiem, Abdallah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the current research, the properties of even-even nuclei with a mass number (A≥100) for (100-12448Cd ) isotopes have been studied. This included distortion parameters () derived ,from an Intrinsic, electric, quadrupole, moments (0 )and deformation ,parameters originate from a reduced ,electric ,transition probability based on the energy of the first excited state (2+).,Roots ,mean ,square radii major and minor of oval axes (a, b) in addition to the difference between them (ΔR) calculated for Cadmium isotopes. All of these parameters were calculated for cadmium isotopes by deforming the model of the shell equation in Matrix laboratory software. Major (a) and minor (b) axes were utilized to plot three-dimensional shapes (axially symmetric) and sketch two-dimensional shapes of the isotopes, allowing for the differentiation of various single-element isotopes. According to the latest research, the deformation parameters get smaller as the neutron count gets closer to the enchanted number of neutrons.